The green economy: The link between corporate social responsibility and financial performance during economic shocks - Donnelly, Myles (Cranfield University, 2015)
A prominent claim within the literature is that ‘green’ firms are fundamentally more resilient to financial, environmental and social shocks, relative to firms that take no environmental action. To test this, this study compared the financial performance of firms in the UK FTSE4good, and similar firms outside the FTSE4Good through selected financial, environmental and social shocks Firstly the FTSE4Good indices were compared to the performance of the FTSE All-Share through several shocks. The results of which indicated through average returns, ranking performance and descriptive statistics that the FTSE4good Benchmark did not provide resilience in excess of the FTSE All-Share. The lack of significance was thought to be the consequence of diversification caused by the heterogeneity of each firm’s core business. The FTSE4good UK 50 showed neither and advantage nor disadvantage in resilience performance relative to the FTSE All-Share but the higher moments in the distribution of the returns (skewness and kurtosis) shows evidence of decreased risk in producing extreme negative returns. Furthermore, the discrepancies were also thought to be a consequence of the level at which FTSE4good include firms in the index series. To account for this discrepancy, FTSE4good’s ESG ratings were used to identify the best in class firms, eliminating middle ground performance. Only firms classified according to social performance showed conclusive evidence of an advantage for investors who could reduce their risk profile by selecting only firms with relatively high social responsibility ratings. The results show that the assumption that green firms are more resilient to shocks is too imprecise, at least when analysed in terms of financial performance across the period covered by this study. To become a more effective indicator of environmental, social and governance performance the FTSE4good must demand higher levels of performance from constituent firms and punish any transgressions more severely.